Development of Local Food Innovation Based on Processed Green Mustard as a Strategy for Enhancing Agricultural Product Value in Desa Cepogo, Boyolali Regency - Husnun, Fadilah; Nuraini, Vivi (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2024)
Desa Cepogo in Boyolali Regency, Central Java, has rich and fertile agricultural potential. Its location at the foot of Mount Merapi and Merbabu results in fertile soil and abundant water, making it suitable for agricultural and livestock activities. One of the main commodities is green mustard plants. However, the occurrence of bountiful harvests in Desa Cepogo village affects the selling prices of various agricultural products, including green mustard plants. Therefore, a solution is needed to process green mustard into higher-value food products. The community service team from FATIPA UNISRI is assisting the local community, particularly the PKK (Family Welfare Movement) mothers, in training them on how to process green mustard into healthy green noodles and vegetable nuggets. The objective of this community service is to reduce the sale of raw agricultural products and instead transform them into finished goods. The training on processing green mustard into finished food products such as green noodles and vegetable nuggets is expected to provide a solution to the existing issues. The expected outcome of this community service is that the people of Desa Cepogo village will be able to process and sell food products made from green mustard at a high selling price, thereby improving overall well-being.